Green Supplier Analysis on Entrepreneur Students - Rahmi Yuniarti (Universitas Muhammadiyah Malang, 2023)
This paper aims to focus on the development of a green supplier selection model using a factor analysis. There are 25 research indicators with 5 classifications. The research was carried out in 3 stages, namely the first stage exploring green supplier indicators, the second stage distributing questionnaires to respondents regarding 25 indicators, and the third processing the data using factor analysis. The research population was entrepreneurial students in Malang because no data on entrepreneurial students was found, the research sample was taken as 30, consisting of 5 respondents from each university. The research results show that 25 indicators are valid and reliable, from a classification of 5 they developed into 8 green supplier selection factors. The 8 factors are: delivery assurance, environmental quality, green assurance, environmental, delivery relationship, cost, conform quality